Code Mixing in Cooking Terms on Jesselyn MCI 8’S Tiktok Account in Gourmet with Jess Segment - Yulianti, Fitri; Dadan Firdaus; Toneng Listiani (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the phenomena of English–Indonesian code mixing in Jesselyn Lauwreen's short-form video material, specifically in her Gourmet With Jess TikTok series. Lauwreen is the winner of MasterChef Indonesia Season 8. The research distinguishes and classifies three linguistic forms—intra-sentential code mixing, intra-lexical code mixing, and code mixing involving pronunciation change—based on Charlotte Hoffman's (1991) typology of code mixing. In order to investigate how English cooking terminology is incorporated into Indonesian narratives, 10 TikTok videos were examined using a qualitative descriptive technique. The results show that the most common technique is intra-sentential code mixing, in which English phrases like